Critical and Transnational Literacies in International Development and Global Citizenship Education - Andreotti, Vanessa de Oliveira (2014)
This article explores the concepts of transnational and critical literacies in developmentand global citizenship education. Critical literacy, as defined in this text, emphasizesthe need for a careful examination of collective social scripts (e.g. of progress,knowledge, belonging, and identity) as a practice of responsible intellectualengagement across all sectors. Transnational literacy is defined as an examinationof the dynamics of globalisation and how it can be negotiated. In the first part ofthis article, I introduce the concept of critical literacy in global citizenship educationoffering examples of my own academic and pedagogical practice in this area.In the second part, I introduce the idea of transnational literacy with examplesfrom international development education. In the last part, I present a cartographywith four different “root” narratives as a stimulus for dialogue and analyses thatuses both critical and transnational literacies and that may clarify concepts andopen new possibilities for thinking and practice in education.